2014
DOI: 10.1002/art.38762
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide DNA Methylation Study Identifies Significant Epigenomic Changes in Osteoarthritic Cartilage

Abstract: Objective. To perform a genome-wide DNA methylation study to identify DNA methylation changes in osteoarthritic (OA) cartilage tissue.Methods. The contribution of differentially methylated genes to OA pathogenesis was assessed by bioinformatic analysis, gene expression analysis, and histopathologic severity correlation. Genome-wide DNA methylation profiling of >485,000 methylation sites was performed on eroded and intact cartilage from within the same joint of 24 patients undergoing hip arthroplasty for OA. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(134 citation statements)
references
References 50 publications
9
124
0
Order By: Relevance
“…Mapping DNA methylation changes in health and disease can inform about disease-associated chromatin structure, and identify epigenetically modified genetic targets that can help to better understand disease pathogenesis and potentially identify novel targets for therapy [5,1215]. Further, the dynamic nature of DNA methylation changes makes them appealing targets to explore as disease biomarkers [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Mapping DNA methylation changes in health and disease can inform about disease-associated chromatin structure, and identify epigenetically modified genetic targets that can help to better understand disease pathogenesis and potentially identify novel targets for therapy [5,1215]. Further, the dynamic nature of DNA methylation changes makes them appealing targets to explore as disease biomarkers [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on genome-wide DNA methylation in AC have focused on either the knee12 23 or hip12 24 joints and more primarily on comparing OA affected with control tissues. Nevertheless, Rushton et al 12 did report epigenetic differences between knee and hip AC at specific CpGs.…”
Section: Discussionmentioning
confidence: 99%
“…DNMT1, however, is largely responsible for maintaining the DNA methylation signatures created by these de novo enzymes during cell division. Recent genome-wide methylation profiling studies have identified differentially methylated loci in the genome of human OA chondrocytes, thereby suggesting the involvement of DNMT-driven mechanisms in the development and/or progression of OA (18,(22)(23)(24)(25)(26). This study was designed to address the potential role of the de novo Dnmt3 enzymes in regulating murine articular cartilage homeostasis.…”
Section: -Methylcytosine (5mc)mentioning
confidence: 99%